STUDENT INTEREST IN ENTREPRENEURSHIP: THE ROLE OF ENTREPRENEURSHIP EDUCATION AND THE ENVIRONMENT OF FAMILY - Syamsul Hidayat; Hertanto Tamba; Abdul Bahits (Yayasan Education and Social Center, 2021)
This study aims to determine the effect of entrepreneurship education and the family environment on the interest in entrepreneurship among university students. The research method used is quantitative. The population in this study was students of the University of Bina Bangsa who had taken the entrepreneurship course, and the sampling in this study used probability sampling using the Slovin formula as many as 110 respondents. The results of this study indicate that partially entrepreneurship education does not affect student interest in entrepreneurship. Somewhat the family environment affects students' interest in entrepreneurship